Impact Assessment of National Village and Urban Community Fund on the Household Financial Stability using Propensity Score Matching and Difference in Difference Model - Piyakarn, Anck; Socatiyanurak, Montree (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
This paper aimed to study the impact assessment of National Village and Urban Community Fund (VF) on the microeconomic in the household sector using business financial ratio that can assess the impacts from the participation explicitly than direct comparison on household financial status. In the Study, the impacts were assessed using the propensity score matching (PSM) and difference in difference (DiD) model with logistic regression model. This study benefited from the Socio-Economic Survey (SES) re-survey (panel data) of the National Statistical Office and population groups were categorized into regions in line with the National Statistic Office, including central (excluding Bangkok Metropolitan Region), northern, northeastern and southern. The results of annual impacts of the study revealed that the financial stability of households borrowing VF is lower than that who did not borrow in terms of liquidity, debt burden, solvency and consumption maintenance. Except the southern area, where the household financial stability that borrowed is not different from those who did not borrow. While DiD model showed that the VF impacts on household financial stability by decline household liquidity of the central and northeastern area, and rising household consumption maintenance of the southern. The long-term VF contract is more likely to increase the risk of household solvency in the central area.